(3PQGY GdcYHIs - (3GdOjGQ HcQj, MSjf Hf eMeO Hf GdMSf, (B966 (3g`s ((3UGbj Hf SdjeGfs)
(3ChdgG (B:s
(3GdMeO ddg agPg QSGdI aj PQGY GdcYHI GdeYXeI heSGMI GdeSLO GdMQGe haj Pdc GYde Cf GdPQGY CQHY hYTQhf CUHYG eVeheI Shi GdEHgGe HYOO LQha dG Edg EdG Gddg eMeO QShd Gddg s
(3BNQgG (B:s
(3hYdi GdUaG hGdeQhI hHjf GdUaG hGdeQhI haj Lha GdcYHI hHefi hHLejY eROdaI hHYQaGJ hYfO GdLeQGJ GdKdGK hYfO ReRe hYOgG ZjQg HgPG GdJQJjH YfO QDjI GdHjJ Jes
(3aj MjGI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\256s
(3GdCYdGe (B2\256s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdLZQGajG hGdHdOGfs